2021
DOI: 10.1212/nxg.0000000000000596
|View full text |Cite
|
Sign up to set email alerts
|

Novel TUBA4A Variant Associated With Familial Frontotemporal Dementia

Abstract: ObjectiveDespite the strong genetic component of frontotemporal dementia (FTD), a substantial proportion of patients remain genetically unresolved. We performed an in-depth study of a family with an autosomal dominant form of FTD to investigate the underlying genetic cause.MethodsFollowing clinical and pathologic characterization of the family, genetic studies included haplotype sharing analysis and exome sequencing. Subsequently, we performed immunohistochemistry, immunoblotting, and a microtubule repolymeriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 41 publications
2
18
0
Order By: Relevance
“…More recently, Mol et al, described another TUBA4A variant (R105C) in a family with different forms of dementia, among which bvFTD with prominent disinhibited behavior and parkinsonian-like gait disturbances [12]. One family member displayed unspecified dementia and comorbid Parkinsonism, and another relative was clinically diagnosed with Parkinson's disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Mol et al, described another TUBA4A variant (R105C) in a family with different forms of dementia, among which bvFTD with prominent disinhibited behavior and parkinsonian-like gait disturbances [12]. One family member displayed unspecified dementia and comorbid Parkinsonism, and another relative was clinically diagnosed with Parkinson's disease.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these mutations occur in the C-terminal end of the protein, which is important for its interaction with other tubulin subunits and associated proteins, such as kinesin [11]. More recently, however, mutations in the N-terminal region of TUBA4A were observed in patients with FTD without motor neuron disease [7,12]. In this report, we present the neuropathological post-mortem analysis of an FTD patient presenting with the semantic variant (svPPA) and an R64Gfs*90 TUBA4A mutation, and suggest reduction of TUBA4A protein levels as a potential pathogenic mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…TUBA4A (tubulin alpha 4a) is the gene that encodes -tubulin. TUBA4A mutations have been linked to neurodegenerative diseases such as amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) [ 34 , 35 ]. Little articles concern TUBA4A in cancer, and only lung cancer was mentioned [ 36 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…SCN3B [405], PCDH19 [406], CNTNAP2 [407], STXBP1 [408], CHRNB2 [409], NAPA (NSF attachment protein alpha) [410], STX1B [411], GABRG2 [412], CAMKK2 [144], CNTNAP2 [413], ARHGEF9 [414], COX8A [415], CALHM1 [416], SLC45A1 [417], TLR5 [418] and KCNJ10 [419] could be acuseful prognostic biomarker in epilepsy. The altered expression of NPTX2 [420], VAMP2 [421], PRKAR1B [422], SNCB (synuclein beta) [199], AP2M1 [423], TUBA4A [424], KIF17 [425] and SYK (spleen associated tyrosine kinase) [426] might be related to the progression of dementia. The above evidence revealed that these genes were related with disorders of the nervous system and might have a function in PD.…”
Section: Discussionmentioning
confidence: 99%